Новые виды рода Menacanthus Neumann (Mallophaga, Menoponidae) от воробьиных птиц Хабаровского края - Федоренко, И.А. (Вестник зоологии, 1978)
Four new species of Mallophaga of the genus Menacanthus parasitizing on Passeriformes of the Khabarovsk Territory are described: M. orientalis sp. n. from Luscinia cyane Pall., M. spodocephalae sp. n. from Emberiza spodocephala Pall., M. chabaroviensis sp. n. from Turdus hortulorum Sclater and M. volkovi sp. n. from Turdus dauma Latham.